2007
DOI: 10.1029/2006gl029152
|View full text |Cite
|
Sign up to set email alerts
|

Modelling vegetated dune landscapes

Abstract: [1] This letter presents a self-organising cellular automaton model capable of simulating the evolution of vegetated dunes with multiple types of plant response in the environment. It can successfully replicate hairpin, or long-walled, parabolic dunes with trailing ridges as well as nebkha dunes with distinctive deposition tails. Quantification of simulated landscapes with eco-geomorphic state variables and subsequent cluster analysis and PCA yields a phase diagram of different types of coastal dunes developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
144
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 21 publications
3
144
1
Order By: Relevance
“…In addition to detecting different successional stages across a vegetated or semi-vegetated dune field, the ability to resolve spatial patterns of vegetation types is important for linking empirical observations with numerical models, and for understanding the degree of forcing that would be required to reactivate stabilized or stabilizing dunes. In the numerical model of Baas and Nield (2007) it was found that the addition of two types of vegetation (shrubs and grasses) was necessary to form realistic parabolic and nebkha dunes. In this regard, multispectral imagery could and should be used to test this parameterization, and if needed, guide the refinement of the numerical growth characteristics.…”
Section: Discriminating Dune Vegetation Soil Crust and Open Sandmentioning
confidence: 99%
“…In addition to detecting different successional stages across a vegetated or semi-vegetated dune field, the ability to resolve spatial patterns of vegetation types is important for linking empirical observations with numerical models, and for understanding the degree of forcing that would be required to reactivate stabilized or stabilizing dunes. In the numerical model of Baas and Nield (2007) it was found that the addition of two types of vegetation (shrubs and grasses) was necessary to form realistic parabolic and nebkha dunes. In this regard, multispectral imagery could and should be used to test this parameterization, and if needed, guide the refinement of the numerical growth characteristics.…”
Section: Discriminating Dune Vegetation Soil Crust and Open Sandmentioning
confidence: 99%
“…In transgressive profiles, Ammophila arundinacea becomes an absolute dominant, not only because of its capability to survive deep sand burial (García-Mora et al 1999, Levin et al 2008), but also due to the reduction or disappearance of other species (as indicated by its negative correlation to other biological metrics; cf. Table 3), possibly due to loss of facilitation efficiency under extreme stress conditions (Brooker et al 2008).…”
Section: Which Features Of Foredune Vegetation Are Most Influenced Bymentioning
confidence: 99%
“…7), even though only a residual percentage (3%) of the compositional variation in the vegetation dataset was found to be due to interactions between biogeography and local dynamics. Nonetheless, even along our narrow biogeographic gradient (ca 200 km long), a decrease in facilitation efficiency under extreme stress conditions (Brooker et al 2008) may be involved in the loss of unspecialized plants ('type I' species of García-Mora et al 1999) related to both biogeography (i.e. water stress gradient due to southwards decreasing rainfall; Forey et al 2008) and local dynamics (i.e.…”
Section: Which Features Of Foredune Vegetation Are Most Influenced Bymentioning
confidence: 99%
See 2 more Smart Citations